The hidden kingdom of fungi : exploring the microscopic world in our forests, homes, and bodies - Seifert, Keith A. (Greystone Books, 2022)
"For readers of Entangled Life and The Hidden Life of Trees comes an illuminating account of the "invisible" fungi that share our world: from the air we breathe to the dust beneath our feet. The Hidden Kingdom of Fungi traces the intricate connections between fungi and all life on Earth to show how these remarkable microbes enrich our lives: from releasing the carbon in plants for the benefit of all organisms to transmitting information between trees, to producing life-changing medicine, to adding umami flavor and B vitamins to our food. Divided into sections, each one exploring an environment where fungi live, this enthralling, science-backed book ventures into our homes, bodies, farms, and forests to profile the fungi that inhabit these environments, most of them invisible to the naked eye. Along the way, the author, the esteemed career mycologist Keith Seifert, explains the latest research into where these fungi came from: how yeast, lichens, slimes, and molds evolved and adapted over millions of years. And he shows us that, surprisingly, fungi share almost a quarter of human genes. We may have more in common with yeast and slime than we think ... But not all fungi are good for us. In fact, fungal diseases lead to over 1 million deaths each year and more than a quarter of our food goes to waste. How can we strike a better balance with our microbial cousins, both for their sake and ours? The Hidden Kingdom of Fungi urges us to better understand our relationship with fungi--and to plan our future with them in mind--while revealing their world in all its beautiful complexity."--